A Theoretical Study of the Ionization States and Electrical Conductivity of Tantalum Plasma - Shi Chen; Qishuo Zhang; Qianyi Feng; Ziyue Yu; Jingyi Mai; Hongping Zhang; Lili Huang; Chengjin Huang; Mu Li (Plasma, 2025)
Tantalum is extensively used in inertial confinement fusion research for targets in radiation transport experiments, hohlraums in magnetized fusion experiments, and lining foams for hohlraums to suppress wall motions. To comprehend the physical processes associated with these applications, detailed information regarding the ionization composition and electrical conductivity of tantalum plasma across a wide range of densities and temperatures is essential. In this study, we calculate the densities of ionization species and the electrical conductivity of partially ionized, nonideal tantalum plasma based on a simplified theoretical model that accounts for high ionization states up to the atomic number of the element and the lowering of ionization energies. A comparison of the ionization compositions between tantalum and copper plasmas highlights the significant role of ionization energies in determining species populations. Additionally, the average electron–neutral momentum transfer cross-section significantly influences the electrical conductivity calculations, and calibration with experimental measurements offers a method for estimating this atomic parameter. The impact of electrical conductivity in the intermediate-density range on the laser absorption coefficient is discussed using the Drude model.